Depletion and development: Natural resource supply with endogenous field opening - Anthony J. Venables (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper develops a model in which supply of a non-renewable resource can adjust through two margins: the rate of depletion and the rate of field opening. Faster depletion of existing fields means that less of the resource can ultimately be extracted, and optimal depletion of open fields follows a (modified) Hotelling rule. Opening a new field involves sinking a capital cost, and the timing of field opening is chosen to maximize the present value of the field. Output dynamics depend on both depletion and field opening, and supply responses to price changes are studied. In contrast to Hotelling, the long run equilibrium rate of growth of prices is independent of the rate of interest, depending instead on characteristics of demand and geologically determined supply.
Keywords: D90; Q30; Q40; Q50; 330; non-renewable resource; depletion; exhaustible; Hotelling; fossil fuel; carbon tax